Spectral efficient and high data rate ring topology based UWOC system with carrier-free optical add-drop nodes - Ammar Armghan; Slim Chaoui; Meshari Alsharari; Khaled Aliqab; Salman Ghafoor; Muhammad Ijaz; Jawad Mirza (PLoS ONE, 2026)
In this paper, we report a ring topology based spectral efficient and high data rate underwater wireless optical communication (UWOC) system transmitting full-duplex data to five different optical add-drop nodes (OADNs) distributed in the ring. The UWOC system is designed so that all five nodes can transmit uplink (UL) channels without requiring optical source. The combined optical signal composed of five different wavelengths each modulated by the downlink (DL) data at the rate of 20 Gb/s using quadrature phase shift keying (QPSK) is transmitted towards the nodes. The DL baseband data is recovered at respective nodes using homodyne detection and the same optical carrier is re-used to transmit the UL data at the rate of 20 Gb/s encoded using on-off keying (OOK) modulation format towards central unit (CU). A specially designed pulse carver based on dual drive Mach-Zehnder modulator (DD-MZM) is employed to implement the transmission of full-duplex data in the ring. Each node in the ring operates at data rate of 20 Gb/s and is located at a fixed distance of 25 m from the next node in the ring. Underwater bubbling induced turbulence is modelled using Gamma-Gamma channel model. The performance of the DL and UL channels is evaluated using Bit-error rate (BER) results obtained for different generation rates of underwater bubbles. The simulation results clearly indicate that target forward-error correction (FEC) BER limit of 3.8 × 10 −3 is achieved for both DL and UL channels under different bubble generation rates. The failure model introduced in proposed study confirms that the system sustains 80% node connectivity under single OADN failure and 100% node connectivity under primary link failure through link redundancy without changing the path inflation. These findings reflect that the proposed ring topology based UWOC system is flexible and resilient to the adverse channel effects, making it a promising solution for high-speed, long-range future Internet of underwater things (IoUT) applications.